Contraceptive use and quality of life among women of reproductive age, attending a general outpatient clinic in a Nigerian tertiary hospital - Salam, Tawakalit O.; Mosuro, Olushola A.; Muyibi, Sufiyan A.; Adetunji, Adedotun A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: In Sub-Saharan Africa, unplanned pregnancies, sexually transmitted infections (STIs) and low use of modern contraceptives are major reproductive health problems affecting women of reproductive age. However, there is evidence of an increase in contraceptive use over the past decade. This study was carried out to assess the pattern of contraceptive use, and its association with quality of life among women of reproductive age, attending a general outpatient clinic, at the University College Hospital (UCH), Ibadan, Nigeria. Methods: A descriptive, cross-sectional study conducted with 323 women aged 15-49 years for three months. Data were retrieved using a semi-structured questionnaire and analyzed using the Statistical Package for Social Sciences (SPSS) version 23. Results: The mean age of the participants was 34.9±8 years. The prevalence of contraceptive use was 43.7%, and out which, 34.4% accounted for modern methods. At least 72.4% ever heard about a method of contraceptive. Male condom was the most heard (96.6%) and most used (39.0%) contraceptive method. Majority of the quality of life parameters had higher mean scores, with significant mean values in vitality and social functioning categories among contraceptive users (72.41±14.82 and 72.07±18.39 respectively, p=0.029) compared with non-contraceptive users. Conclusions: Despite a higher mean quality of life scores among contraceptive users, less than half of the respondents made use of contraceptives. Therefore, the need for more orientation on the use of contraceptives to promote safe sexual practice and birth control is required.